Example-based learning: The benefits of prompting organization before providing examples. (June 2017) - Roelle, Julian; Hiller, Sara; Berthold, Kirsten; Rumann, Stefan
Abstract: Example-based learning often follows a design in which learners first receive instructional explanations that communicate new principles and concepts and second examples thereof. In this setting, using the knowledge components of the instructional explanations to explain the examples (i.e., generating principle-based self-explanations) is considered to be a highly important learning process. However, a potential suboptimality of this learning process is that it scarcely requires learners to organize the content of the instructional explanations into coherent mental representations. Thus, in two experiments we investigated whether prompting learners to organize the content of the instructional explanations before providing them with the examples (and self-explanation prompts) enhances the effectiveness of example-based learning. We consistently found that organization prompts fostered learning regardless of whether the learners also received self-explanation prompts. Hence, in example-based learning, learners should be prompted to not only generate principle-based self-explanations but also to organize the content of the instructional explanations. Highlights: We found beneficial effects of organization prompts in example-based learning. The benefits occurred regardless of whether self-explanations were prompted as well. The benefits were more pronounced on a delayed than on an immediate posttest. Enhanced organizational processing mediated the benefits of the organization prompts.